ChemInform Abstract: Identification and Antifeedant Activities of Limonoids from Azadirachta indica. Issue 49 (December 2015) - Yan, Yu‐Xin; Liu, Jie‐Qing; Wang, Hong‐Wei; Chen, Jin‐Xiong; Chen, Jian‐Chao; Chen, Li; Zhou, Lin; Qiu, Ming‐Hua
Abstract: isolation and structure elucidation of four new limonoids, azadiraindins A—D from neem tree Azadirachta indica